Triclinium Trialectics: The Triclinium as Contested Space in Early Roman Palestine. (January 2020) - Keddie, G. Anthony
Abstract: This study draws on critical spatial theory to analyze the earliest archaeological and literary evidence of the triclinium, or Roman dining room, in Early Roman Palestine. It begins by examining the archaeological evidence of triclinia and similar banqueting spaces in Palestine, addressing their dating, their differing settings, and how their appearance and diffusion reflects socioeconomic and cultural changes under Roman influence. Next, it examines literary constructions of banqueting spaces in the Parables of Enoch, Testament of Moses, and "Q Sayings Gospel." It demonstrates that these sources all seem to envision a triclinium setting in which elites eat, drink, and engage in all sorts of revelry while reclining on couches. The final section is devoted to critical spatial analysis of both the archaeological and literary data. It argues that these sources all evince, in varying ways, the interpenetration of local and global spaces rather than the unilateral "Romanization" of provincial space.